2014
DOI: 10.1287/opre.2013.1248
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Benders' Cuts for the Strip Packing Problem

Abstract: We study the strip packing problem, in which a set of two-dimensional rectangular items has to be packed in a rectangular strip of fixed width and infinite height, with the aim of minimizing the height used. The problem is important because it models a large number of real-world applications, including cutting operations where stocks of materials such as paper or wood come in large rolls and have to be cut with minimum waste, scheduling problems in which tasks require a contiguous subset of identical resources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 43 publications
1
78
0
Order By: Relevance
“…Constraints (10) ensure that the active workstations are in an ordered sequence. Constraint sets (11), (12) and (13) order tasks and assign setup operations between them if they are assigned to the same workstation. Any two tasks have to be ordered within a workstation due to their precedence relations which is ensured by constraints (14).…”
Section: B Ijmnmentioning
confidence: 99%
See 2 more Smart Citations
“…Constraints (10) ensure that the active workstations are in an ordered sequence. Constraint sets (11), (12) and (13) order tasks and assign setup operations between them if they are assigned to the same workstation. Any two tasks have to be ordered within a workstation due to their precedence relations which is ensured by constraints (14).…”
Section: B Ijmnmentioning
confidence: 99%
“…As stated by Côté et al, [11], for a special case of P where c = 0, the slave SP can be used as a feasibility check on the system {Ay + Bx ≥ b, y ≥ 0}. In particular, ifx is not a feasible solution for at least one variable x j causing infeasibility, then this variable must take a different value fromx j .…”
Section: A Benders Decomposition Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…They solved the slave problem by logical deduction methods, such as constraint programming, whose outcome was used to produce valid cuts. Côté et al [83] also used Benders' decomposition where both subproblems were MILPs solved by combinatorial algorithm. To produce effective valid cuts, they used the combinatorial Benders' cuts introduced by Codato and Fischetti [69], in which a third combinatorial algorithm is used to find the cuts that are added to the master.…”
Section: Introductionmentioning
confidence: 99%
“…The latter also made computational experiments on SPP instances, but the results were not encouraging, as the proposed approaches generally perform worse than the 'old' Martello et al [212] branch-and-bound algorithm. Côté et al [83] found better results by using a Benders' decomposition in which the master problem is a MILP model and the slave is solved through branch-and-bound.…”
mentioning
confidence: 99%